Characterization of estrogen receptor ßb in sea bream (Sparus auratus): phylogeny, ligand-binding, and comparative analysis of expression - Pinto, Patricia IS (2014)
Estrogens control many physiological processes in both female and male vertebrates, mostly mediated by speciWc nuclear estrogen receptors (ER). Two ER subtypes (ER and ER ) are present in most vertebrates, including the sea bream (Sparus auratus) a hermaphrodite teleost Wsh. In the present study several variant cDNAs encoding a second sea bream ER (sbER b) is reported. Phylogenetic and Southern blot analysis indicate that sbER b and the previously cloned sbER a (formerly sbER ) are encoded by diVerent genes, which may have arisen by duplication of an ancestral ER gene. Competitive binding assays show that sbER b has high aYnity for 17 -estradiol (KdD1 nM) and speciWcally binds estrogen agonists (diethylstilbestrol and ethynylestradiol) and antagonists (ICI 182,780). In Northern blot sbER , sbER a, sbER b produce several diVerent transcripts in a variety of tissues. RT-PCR showed a partially overlapping but diVerential tissue distribution in both male and female sea bream.